𝑝-Wave Pairing in Quantum Hall Bilayers - Z. Papić; M. V. Milovanović (Advances in Condensed Matter Physics)
We show that the wave functions that describe the ground states of putative 𝑝-wave-paired phases in quantum Hall bilayers, like the Pfaffian at 𝜈𝑇=1/2 or the paired phase at 𝜈𝑇=1, are more likely to describe the excited states of Fermi liquids at these filling factors. We point out to the close competition between Fermi liquid and paired phases, which leads to the conclusion that in the experiments only direct transitions from the correlated 111 and 331 states into Fermi liquid(s) are likely to be observed.